2010
DOI: 10.2165/11530220-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Lennox-Gastaut Syndrome

Abstract: Lennox-Gastaut syndrome occurs in 3% of children with epilepsy and is characterized by multiple seizure types, slow spike-and-wave discharges and a poor prognosis for seizure control and cognitive development. Although randomized controlled trials of adjunctive felbamate, lamotrigine, topiramate and rufinamide have demonstrated a > or =50% reduction in seizure frequency, very few children achieve complete seizure control and a Cochrane review of the treatment of Lennox-Gastaut syndrome concluded that the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 85 publications
0
40
0
5
Order By: Relevance
“…The mean steady-state plasma rufinamide concentration that would reduce the frequency of tonic and or Table I. Comparison of the efficacy and tolerability of major antiepileptic drugs (AEDs) used in patients with Lennox-Gastaut syndrome [2,5] [12] The concentration that would reduce the tonic and or atonic seizure frequency by 25% would be about 20 mg mL, which is within the range reached by patients in clinical studies. [9] Clinical trials have shown that at dosages of 40 mg kg day the mean plasma steady-state rufinamide concentration was approximately 15 mg mL (table III).…”
Section: Pharmacodynamic Profile Mechanism Of Actionmentioning
confidence: 87%
See 2 more Smart Citations
“…The mean steady-state plasma rufinamide concentration that would reduce the frequency of tonic and or Table I. Comparison of the efficacy and tolerability of major antiepileptic drugs (AEDs) used in patients with Lennox-Gastaut syndrome [2,5] [12] The concentration that would reduce the tonic and or atonic seizure frequency by 25% would be about 20 mg mL, which is within the range reached by patients in clinical studies. [9] Clinical trials have shown that at dosages of 40 mg kg day the mean plasma steady-state rufinamide concentration was approximately 15 mg mL (table III).…”
Section: Pharmacodynamic Profile Mechanism Of Actionmentioning
confidence: 87%
“…This disorder is usually observed in children aged between 2 and 8 years, with a peak incidence around 5 years of age. [2] Clinicians postulate that this syndrome can originate from different etiologies: cortical dysplasia, neurometabolic disorders, traumatic and hypoxic brain insult, and infection such as encephalitis. [3] Patients with Lennox-Gastaut syndrome can have various generalized seizure types, such as atonic and myoclonic, tonic-clonic, and atypical absence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LGS is identified by its characteristic triad of symptoms, including multiple generalized seizure types, a slow spike and wave (≤2.5) pattern in the awake electroencephalogram, and cognitive decline. The types of seizures most commonly associated with LGS are tonic, atypical absence, myoclonic, and atonic seizures,5,6 but many LGS patients also experience generalized tonic-clonic and focal seizures 2,4,6,9,10. In addition to the slow spike and wave pattern, bursts of paroxysmal fast activity during sleep are also classically present on the electroencephalogram and may be associated with subtle tonic seizures 1,5,6.…”
Section: Lennox–gastaut Syndromementioning
confidence: 99%
“…LGS is resistant to treatment and often, in part due to the multiple seizure types, a combination of antiepileptic drugs is required 3,68,12. LGS is considered an epileptic encephalopathy, in which the degree of cognitive deterioration present is thought to be related to seizure frequency and burden of epileptic discharges 4,5,11…”
Section: Lennox–gastaut Syndromementioning
confidence: 99%